Drivers for authenticity: student approaches and responses to an authentic assessment task. Issue 7 (3rd October 2021) - Colthorpe, Kay; Gray, Harrison; Ainscough, Louise; Ernst, Hardy
Abstract: Authentic assessment has long been recommended as valuable for engaging and motivating students. However, given the choices available to students in completing authentic tasks, the products of such assessment may vary in authenticity. This study aimed to evaluate the authenticity of students' assessment products and their perceptions regarding the task. Occupational therapy students created an information sheet for other health professionals about a disease or condition, and were awarded marks for content but not presentation. The students' products ( n  = 59) were evaluated for authenticity using a novel rubric developed during this study. Students' perceptions regarding what made their information sheet real and their approach to creating it were also evaluated. The authenticity of the information sheets was variable, with most having moderate to high authenticity. However, there was no correlation between authenticity and course grade. Students said the presentation and content of their information sheets increased its realism, and that they were influenced by a desire to provide information appropriate for their target audience. Few were deterred by the lack of presentation marks. When given choice over product design, students tend to create products that are authentic. They are strongly influenced by the defined audience, despite the challenge this poses.